Development of an elective course on dietary supplements for undergraduate college students - Tyler B. Becker; Jenifer I. Fenton; Eric A. Gurzell (Cogent Public Health)
Due to little dietary supplement regulation and misinformation online, there is a need to educate consumers on them, which could be addressed using a higher education course to provide students resources to evaluate supplement information. The objective of this paper was to describe the design of a 3-credit dietary supplement elective course (HNF 102- Dietary Supplements: Evidence vs Hype) for undergraduate students. Furthermore, to analyze student perspectives and skills developed resulting from course completion. HNF 102 is a 5-unit asynchronous online course which consists of the following units: Unit (1) provides an overview of nutrition and dietary supplements; Unit (2) describes dietary supplement regulation; Unit (3) provides credible sources of dietary supplement information and tools to evaluate dietary supplement information; Unit (4) describes research on dietary supplements claimed to improve general health; Unit (5) describes research on dietary supplements purported to improve performance. A process evaluation inquiring about student opinions following course completion was offered as an extra credit opportunity. Overall, students indicated course lecture materials and assignments improved their understanding of dietary supplements and their ability to evaluate dietary supplement information. Dietary supplement undergraduate courses can be an effective method to improve consumer dietary supplement health literacy.